Development of A Simple Method for The Detection of Phosphorus Insecticides - Yarman, Aysu; Afsar, Huseyin (ASIAN JOURNAL OF CHEMISTRY, 2010)
In this study, a detection method was developed for phosphorus insecticides. At first phosphomolybdate was formed by using standard phosphate solution and ammonium molybdate and then it was reduced to obtain molybdenum blue. According to the earlier experiments. in-phenylenediamine, which hadn't been used classically as a reductant, was tested and at the first part of this study a phosphate detection method was developed by using this reductant. The optimum pH range was found for the reduction of phosphomolybdate as 1-1.5 and as 5-6 for the formation of molybdenum blue, respectively. The maximum absorbance was measured between 705 rim and 710 nm and the molar absorptivity coefficient was calculated in terms of phosphorus as 2.95 x 10(-3) L/mol cm, At the second part of this study, developed method Was used for the detection of two pesticides, dimethoate and methyl parathion. Before reacting with ammonium molybdate, pesticides were degraded in alkaline conditions with hydrogen peroxide to form phosphate.
Keywords: Phosphorus pesticides; Molybdenum blue; m-Phenylenediamine; Phosphate; Chemistry